The Dynamic Regulation of mRNA Translation and Ribosome Biogenesis During Germ Cell Development and Reproductive Aging - Mercer, Marianne; Jang, Seoyeon; Ni, Chunyang; Buszczak, Michael (Frontiers in Cell and Developmental Biology, 2021)
The regulation of mRNA translation, both globally and at the level of individual transcripts, plays a central role in the development and function of germ cells across species. Genetic studies using flies, worms, zebrafish and mice have highlighted the importance of specific RNA binding proteins in driving various aspects of germ cell formation and function. Many of these mRNA binding proteins, including Pumilio, Nanos, Vasa and Dazl have been conserved through evolution, specifically mark germ cells, and carry out similar functions across species. These proteins typically influence mRNA translation by binding to specific elements within the 3’ untranslated region (UTR) of target messages. Emerging evidence indicates that the global regulation of mRNA translation also plays an important role in germ cell development. For example, ribosome biogenesis is often regulated in a stage specific manner during gametogenesis. Moreover, oocytes need to produce and store a sufficient number of ribosomes to support the development of the early embryo until the initiation of zygotic transcription. Accumulating evidence indicates that disruption of mRNA translation regulatory mechanisms likely contributes to infertility and reproductive aging in humans. These findings highlight the importance of gaining further insights into the mechanisms that control mRNA translation within germ cells. Future work in this area will likely have important impacts beyond germ cell biology.